Persepsi Pembelajaran Berbicara Elaborasi Kreatif Kritis Stimulasi Model Challenge Based Learning - Kartika, Pheni; Rachmawati, Dian Karina; Ngatmain, Ngatmain (Universitas Muhammadiyah Surabaya, 2024)
This study aims to analyze the implementation of creative, critical speaking skills learning with the Challenge Based Learning model, as well as evaluating student perceptions of speaking learning in speaking skills courses. This research uses qualitative approach with survey model. The subjects of this study were 40 2nd semester students consisting of Indonesian Language and Literature Education Study Program students and English Education students of FKIP UMSurabaya. The instruments used were observation, questionnaires with questions about critical creative speaking. The results of the analysis of the implementation of this activity show that student learning gained new knowledge about how to improve critical creative thinking skills through the Challenge Based Learning model. The results of the questionnaire provided obtained information that students gave a positive response (84%) and gave the opinion that the ability to speak critically creatively can be done at the level of students with any character, and is considered to improve the ability to think creatively. In addition, this activity with the elaboration of critical creative learning and challenge-based learning model produces creative speaking skills, which can then be implemented by students in teaching speaking to students when they become professional teachers.